STUDI POTENSI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DI SUNGAI CIKAWAT DESA TALANG MULIA KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN PROPINSI LAMPUNG - . Sulistiyono; Agus Sugiri; A.Yudi Eka Risano (Jurnal Ilmiah Teknik Mesin, 2013)
Electric was the vital energy and needed by community for all activity as lighting, radio, television (information), industry , etc. Although aspecialy the urban community was needed this energy and a little rural community was needed. There was several isolated villages in Pesawaran sub province , no electricity by PLN. For this villages goverment would supply the elerctric energy and build microhydro electric plant. The purpose of this with title “Feasibility Study Micro Hydroelectric Power Station (PLTMH) at cikawat river in talang mulia village pesawaran sub province” is to contributed in hydro turbine management and to planning a micro hydroelectric power station that can be used and applied for a better life The research was carried out by using a very simple method is to use a floating object method to measure discharge and plastic hose method for measuring head.Based on the field data, (Head efektif = 9. 35m and water debt = 0,1029 m3/s) the crossflow Turbine can produce energy 7.07 kW. Bellow to the data above it is result that the cikawat river can be set a micro hydro electric power.Keywords : micro hydroelectric power station, water dept, crossflow Turbine.